Efektivitas Bimbingan Kelompok dengan Teknik Problem Solving untuk Meningkatkan Keterampilan Belajar Siswa Madrasah Aliyah Negeri 3 Medan - Adinda Salsameywa Putri; Alfin Siregar; Ali Daud Hasibuan (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
This research aims to see whether group guidance using problem solving techniques can improve students' learning skills at Madrasah Aliyah Negeri (MAN) 3 Medan. This research uses quantitative methods with a quasi-experimental approach, non-equivalent control group design. In this design, both groups (experimental and control) underwent an initial test (pre-test) and a final test (post-test), but only the experimental group was given treatment, while the control group was not given treatment. The research population consisted of students in class X-1 (30 students) and X-2 (30 students). The sample was selected using a purposive sampling method, with a total of 16 students who had low learning skills, namely 8 students from the experimental group (class X-2) and 8 students from the control group (class X-1). The research instrument is a learning skills questionnaire with 26 statements whose validity and reliability have been tested. Data were analyzed using the T-test. The T-test results showed that the experimental group experienced an increase in learning skills, with a significance value of 0.000 < 0.05. This means that problem solving techniques are effective in improving students' learning skills. In contrast, the control group did not show a significant increase in learning skills, with a significance value of 0.022 > 0.05. The results of the independent sample t-test show a significance value (2-tailed) of 0.000 <0.05, which means there are differences in students' learning skills before and after being given services in the experimental group.